Functional p53 can modulate the relationship between E2F-1 expression and tumor kinetics in Hodgkin lymphoma. Issue 3 (March 2015) - Georgiadi, Eleni C.; Dimtsas, Georgios S.; Vassilakopoulos, Theodoros P.; Pangalis, Gerassimos A.; Kittas, Christos; Doussis-Anagnostopoulou, Ipatia A.
Abstract: E2F-1 is the best-described member of the E2F family of transcriptional factors and is particularly interesting in view of its often opposing roles. Our purpose was to examine the immunohistochemical expression of E2F-1 in Hodgkin lymphoma (HL) and to correlate it with proliferation and apoptosis of the tumor, clinicopathological parameters and patient outcome, as well as with expression of the downstream molecules p53 and p21. The median percentage of E2F-1-expressing Hodgkin Reed–Sternberg (HRS) cells was 80.2%. A significant positive correlation was found between expression of E2F-1 and p53 ( p = 0.034). Following stratification of our cases, within the group harboring functional p53, a statistically significant inverse correlation was identified between E2F-1 and Topo IIa ( p = 0.019). E2F-1 is up-regulated in the context of HL and its expression is inversely associated with proliferation. It seems that functional p53 can modulate the relationship between E2F-1 expression and tumor kinetics in HL.